Relationship Analysis of Supervision Implementation of CPPT In General Hospital University Riau - Wanti, Vivi; Arif, Yulastri; Murni, Dewi (Journal Research of Social Science, Economics, and Management, 2022)
Documentation is a means of affective communication between health professions. The low quality of integrated record documentation in Indonesia includes incomplete CPPT where patient identity, date and time of visit are not filled in, PPA's signature and full name, and lack of discipline in filling out medical records by PPA. Supervision is carried out in stages in the preparation, implementation and evaluation phases. The preparation phase contains the planning of the supervision program that will be carried out. The implementation phase is the nurse's assessment by the supervisor while the last phase is the evaluation of the supervision assessment (from the results of direct and indirect observations from the CPPT. The purpose of the thesis is to analyze the relationship between the implementation of supervision on CPPT at the Riau University General Hospital. This study was conducted with a cross sectional approach and is a quantitative study. The research sample is 33 people with total sampling sampling technique. The study uses questionnaires and observation sheets that have been tested for validity and reliability. Through statistics there is a relationship between the preparation phase (p value 0.000), the implementation phase (p value 0.001) and the evaluation (p value 0.000) clinical supervision model 4S with CPPT. Researchers recommend the role of supervision to improve service quality and completeness of integrated recording documentation, carried out by increasing the frequency of supervision and assessment of the implementation of the document integrated logging entity.